Pengetahuan Investasi Memediasi Pengaruh Pepresepsi Return Dan Risiko Terhadap Minat Investasi Mahasiswa - Wasti Reviandani (Jurnal Manajerial, 2023)
Background - Students are part of the community who are studying higher education and are expected to be an example for other people in investing, the investment level is still low, it is necessary to improve so that the investment interest of the community, including students, can increase in the future. Aim - The purpose of this study was to determine whether the perception of return and risk as well as the mediation of investment knowledge can influence students' investment interest. Design / methodology / approach - The research approach is quantitative and data is obtained from distributing questionnaires which are then processed using data analysis techniques using the SEM (Structural Equation Modeling) model using the SmartPLS 3.0 (Partial Least Square) program. Findings - Based on the results of the analysis it is proven that students' perceptions of returns and investment risks have an effect on investment intentions. Investment knowledge has a significant effect on investment knowledge, this empirical result means that the higher students understand returns and risks, and know about investment, the higher the interest in investing in students. Student investment knowledge is proven to be able to mediate the effect of perceived returns and investment risks on investment intentions. Proven student investment knowledge will have an indirect impact on student investment interest. Conclusion - The results of this study indicate that student knowledge is one of the most important factors to increase interest in investing. The earlier we invest, the better prepared we are to face the challenges and risks that may arise in the future. Research implications - Investment is something that students need to study in order to know the right investment and provide long-term benefits. Basically, people who invest are a sign that the person has prepared himself to face the changing economy of a country, so that by preparing himself to face things that are not desirable in the future, especially related to the economy. This research also contributes to science, especially financial management, the results of this study provide a perspective where investment interest is not focused on returns and risks, but requires knowledge about investment. Research Limitations - This research has limitations, namely the population and sample are only focused on UMG 2019 management study program students and cannot be averaged with other objects, future researchers are expected to expand the sample with a wide coverage so that this research can be applied in general.